THE EFFECT OF HOUSEHOLD CONSUMPTION, POPULATION AND GOVERNMENT EXPENDITURES ON REGIONAL ORIGINAL INCOME IN THE MAMINASATA REGION 2014-2018 (Case Study of 4 Regencies/Cities: Makassar, Maros, Gowa, and Takalar) - Hakib, Andi; Asdar, Asdar (Jurnal Ekonomi Balance, 2020)
This research aims to determine the influence of household consumption, population, and government spending on local native income in maminasata area period 2014-2018 (case study of 4 districts / cities: makassar, maros, gowa and takalar). This research uses quantitative methods with secondary data acquisition and collection. Secondary data is a source of data obtained from research through data acquisition. The population in this study is all data from the number of Household Consumption, Population, Government Expenditure and Local Indigenous Development in MAMINASATA Region. Meanwhile, the sample is a set of parts of the population that is expected to represent the research population. Sampling based on the variables used, namely Household Consumption, Population, Government Expenditure, and Local Native Income during the period 2014-2018 in MAMINASATA Region. The results of this study show that household consumption has a positive and significant effect on the local native income, the population has no effect on the local native income, and government spending has a negative and significant effect on the local native income in maminasata region.